Red giant mass-loss : studying evolved stellar winds with FUSE and HST / STIS - Crowley, Cian (Trinity College (Dublin, Ireland). School of Physics, 2006)
The changes that a star undergoes during the dying process are the most dramatic of its lifetime. These changes result in the most important interactions between a star and its environment, indeed it is in this area of research that some of the most challenging astrophysical problems still remain. For most stars, mass-loss becomes significant when they approach the end of their lives and enter the red giant evolutionary phase. This mass is lost in the form of a relatively dense and slow-moving wind which enriches the interstellar medium with material that has been processed inside the star and which is required for the formation of new stars and planets. However, despite the importance and ubiquity of these winds much remains unknown about the outflow conditions and characteristics and, furthermore, the physical processes which drive the mass-loss are unknown. Indeed, the mass-loss question remains arguably the most important outstanding problem of stellar astrophysics. For isolated giant stars, the diagnostics that can be obtained from observations are limited, with only disk-averaged information being directly observable. Spatially resolved observational constraints, in particular within the wind acceleration zone at the base of the outflow and close to the stellar photosphere, are required.
Keywords: Physics, Ph.D.; Ph.D. Trinity College Dublin